Short communication: Molecular characterization of dog and cat p65 subunits of NF-kappaB. (April 2015) - Ishikawa, Shingo; Takemitsu, Hiroshi; Li, Gebin; Mori, Nobuko; Yamamoto, Ichiro; Arai, Toshiro
Highlights: Revealed the full length of the cDNA sequences of dog and cat p65 subunits of NF-κB. Dog and cat p65 subunits of NF-κB showed high sequence homology with other mammalian cells. Dog and cat p65 subunits of NF-κB increased NF-κB transactivation. Dog and cat p65 subunits of NF-κB up-regulated pro-inflammatory cytokine expression. Abstract: Nuclear factor kappa B (NF-κB) plays an important role in the immune system. The p65 subunit is an important part of NF-κB unit, and studies of dog and cat p65 subunits of NF-κB (dp65 and cp65) are important in understanding their immune function. In this study, we described the molecular characterization of dp65 and cp65. The dp65 and cp65 complementary DNA encoded 542 and 555 amino acids, respectively, showing a high sequence homology with the mammalian p65 subunit (>87.5%). Quantitative polymerase chain reaction revealed that the p65 messenger RNA is highly expressed in the dog stomach and cat heart and adipose tissue. Functional NF-κB promoter-luciferase reporter vectors revealed that our isolated dp65 and cp65 cDNA encodes a functionally active protein. Transiently expressed dp65 and cp65 up-regulated pro-inflammatory cytokine expression levels in dog and cat, respectively. These findings suggest that dp65 and cp65 play important roles in regulating immune function.